Safety of a change in specifications of the novel food oleoresin from Haematococcus pluvialis containing astaxanthin pursuant to Regulation (EU) 2015/2283 - EFSA Panel on Nutrition, Novel Foods and Food Allergens (NDA); Dominique Turck; Torsten Bohn; Jacqueline Castenmiller; Stefaan De Henauw; Karen Ildico Hirsch‐Ernst; Alexandre Maciuk; Inge Mangelsdorf; Harry J McArdle; Androniki Naska; Carmen Pelaez; Kristina Pentieva; et al. (EFSA Journal, 2023)
Abstract Following a request from the European Commission, the EFSA Panel on Nutrition, Novel Foods and Food Allergens (NDA) was asked to deliver an opinion on the safety of a change of specifications of the novel food (NF) oleoresin from Haematococcus pluvialis containing astaxanthin (ATX) pursuant to Regulation (EU) 2015/2283. The NF is already authorised as ingredient for the use in food supplements as defined in Directive 2002/46EC in accordance to Regulation (EU) 2017/2470. The NF concerns an oleoresin which contains ~ 10% ATX, obtained by supercritical CO2 extraction of the homogenised and dried biomass of cultivated H. pluvialis. This NF has been assessed by the Panel in 2014. With the present dossier, the applicant proposed to lower the minimum specification limits for protein and ATX monoesters for the NF, and to increase the maximum specification limit for the relative amount of ATX diesters in total ATX. An increase of the maximum specification limit for the 9‐cis isomer is also applied for. Although the data are limited regarding bioavailability and distribution in humans of these three naturally occurring ATX isomers, the available in vitro and in vivo data suggest that the 13‐cis rather than the 9‐cis ATX is selectively absorbed, i.e. has a higher bioavailability and/or possibly emerges from isomerisation of all‐trans ATX. The Panel notes that the toxicity of the individual ATX isomers has not been studied individually. However, the ADI of 0.2 mg/kg, which was established for synthetic ATX and ATX from H. pluvialis, applies also for ATX in the oleoresin from H. pluvialis with the proposed changes of specifications. The Panel concludes that the NF, oleoresin from H. pluvialis containing ATX, is safe with the proposed specification limits.